2013
DOI: 10.1128/aac.01480-13
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Emergence of Colistin Resistance in Klebsiella pneumoniae Producing KPC-Type Carbapenemases Mediated by Insertional Inactivation of the PhoQ/PhoP mgrB Regulator

Abstract: e Colistin is one of the few agents that retain activity against extensively drug-resistant strains of Klebsiella pneumoniae producing KPC-type carbapenemases (KPC-KP). However, resistance to colistin is increasingly reported among KPC-KP. Comparative genomic analysis of a pair of sequential KPC-KP isolates from the same patient including a colistin-susceptible isolate (KKBO-1) and a colistin-resistant isolate (KKBO-4) selected after colistin exposure revealed that insertional inactivation of the mgrB gene, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
298
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 333 publications
(319 citation statements)
references
References 35 publications
15
298
2
4
Order By: Relevance
“…Genomic analysis aimed at detecting the determinants for this resistance trait found that the 10 resistant isolates demonstrated insertion of an IS5-like transposon in the mgrB, a gene that regulates a pathway of lipopolysaccharide biosynthesis (43). Insertion of an IS5-like sequence in the mgrB gene has indeed been proposed as a determinant of colistin resistance (32). Our results appear to support this causative link, considering that none of the six colistin-sensitive strains presented the aforementioned insertion.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Genomic analysis aimed at detecting the determinants for this resistance trait found that the 10 resistant isolates demonstrated insertion of an IS5-like transposon in the mgrB, a gene that regulates a pathway of lipopolysaccharide biosynthesis (43). Insertion of an IS5-like sequence in the mgrB gene has indeed been proposed as a determinant of colistin resistance (32). Our results appear to support this causative link, considering that none of the six colistin-sensitive strains presented the aforementioned insertion.…”
Section: Discussionsupporting
confidence: 75%
“…All colistin-resistant strains harbored a variant of the mgrB gene interrupted by an IS5-like transposon ( Table 3). Insertion of a transposon in this gene has been reported as a determinant of colistin resistance (32).…”
Section: Species Identification and Antimicrobial Susceptibilitymentioning
confidence: 99%
“…However, excessive use of colistin has led to resistance to this drug [13]. The resistance to colistin seen in K. pneumoniae strains is reported to be due to reduced affinity of colistin to lipopolysaccharide target [5]. In this study, colistin resistance in CRKP strains has been identified and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of increased use of carbapenems, carbapenemases are widespread in Enterobacteriaceae family and particularly in Klebsiella pneumoniae; so effective treatment options are decreasing [2,4]. Carbapenemase-producing K. pneumoniae emerged in the late 1990s and has become a serious health problem worldwide [5].…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of the mgrB gene, which encodes a negative feedback regulator of the PhoQ/PhoP signal transduction system, was found to be one of the most common mutational mechanisms responsible for polymyxin resistance among clinical isolates of CRKP (12)(13)(14). Alterations of the PmrA/PmrB and other twocomponent signal transduction systems have also been identified as causes of polymyxin resistance in K. pneumoniae (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%